The Role of Religious Extracurriculars in Improving Student Worship Discipline at MTS Al-Huda East Lampung - Rifai, Arif; Ehwanudin, Ehwanudin; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to analyze the role of religious extracurricular activities in improving students' religious discipline at MTs Al-Huda and identify supporting and inhibiting factors in their implementation. Religion-based character education is an important aspect in forming students' religious awareness, especially in facing the challenges of modernization and globalization. This research uses a qualitative approach with observation, interviews and documentation methods. The research sample consisted of three (3) teachers and six (6) students who were involved in religious extracurricular activities. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions to obtain comprehensive results. The research results show that religious extracurricular activities, such as reading and writing the Koran (BTQ), tahlil, and the practice of caring for corpses, contribute to improving students' religious discipline. Apart from that, this activity also helps students develop leadership, communication and empathy. Some students feel more confident, disciplined, and able to actively participate in social religious activities. However, there are still obstacles, such as a lack of supervisors, as well as students' internal obstacles, such as shyness and lack of confidence in reading the Koran. This research confirms that religious extracurricular activities not only play a role in improving religious discipline, but also shape students' overall character. Through active involvement in these activities, students gain valuable experience in applying spiritual values in everyday life, increase self-motivation, and build leadership and social skills.